Preparation and characterisation of soluble CLIC1 and liposomes - Adamson, Roslin Jane (My University, 2009)
CLIC1 is an intracellular membrane protein that has the intriguing property of being able to exist in both soluble and integral membrane forms. It is unknown how CLIC1 converts from a soluble to a membrane-inserted conformation, but it has been proposed that the transition involves the unfolding of certain regions of the protein followed by refolding into a membrane-competent form. This study characterised the structure and stability of reduced, soluble CLIC1 at the pH values it would encounter in both bulk cytosol and at the membrane surface. Additionally, the preparation and properties of a model membrane system were characterised. At pH 7.0 CLIC1 is more stable and follows a cooperative twostate unfolding transition with a G(H2O) of 10.3 kcal/mol and m-value of 2.3 kcal/mol M-1 urea. At pH 5.5 the CLIC1 native structure is looser and more flexible with lower secondary structural content, is less stable, and unfolds via a stable intermediate with exposed hydrophobic surfaces. The G(H2O) and mvalues for formation and unfolding of this species are well into the dimeric range, and data from the local probe, Trp35, indicate that the intermediate may be oligomeric. The existence of the intermediate species at low pH and under mild denaturing conditions suggests a mechanism whereby CLIC1 may form channels in vivo. Anionic large unilamellar vesicles prepared with a 4:1:1 molar ratio of phosphatidylethanolamine, phosphatidylserine and cholesterol, respectively, were stable up to approximately 50 °C and were highly reproducibly and homogenously sized at ~200 nm diameter. Basal leakage of encapsulated chloride-sensitive fluorescent dye at room temperature was modest for two to three days, and was minimal for up to seven days at 4 °C. These vesicles should prove to be an ideal membrane system for the study of membrane-inserted CLIC1 and with encapsulation of a chloride-sensitive dye may provide the means for a viable functional assay for CLIC1 channel activity.